Argatroban Safe and Promising as Monotherapy or Combined with Tissue Plasminogen Activator - Parry, Nicola (MD Conference Express, 2014)
This article presents data from three clinical trials, and also discussed off-label use of argatroban for ischemic stroke. The results demonstrated positive clinical outcomes, indicating that argatroban appears to be safe and promising, both as monotherapy and in combination with intravenous tissue plasminogen activator (t-PA) for patients with ischemic stroke.